Alternative Energy from Banana Peel Waste Through Natural Process - Othman, Mohamad Izwan; Bahari, Azlina; Abd Wahab, Zurina (Progress in Engineering Application and Technology, 2022)
The term "alternative energy" refers to energy derived from sources other than fossil fuels. The challenge for the current situation is the price of the battery nowadays is getting expensive. The reason it can be expensive is because of the manufacturing process. The aim of this study is to identify a natural process that can convert peel waste into anode material. This study focuses on using biomaterials from banana peel waste to make carbon-based materials for batteries, which might help us utilize less alkali metal in our batteries. 1kg of banana peel waste was collected, dried, and grinded until it become ash and placed in a glass jar. The jar was then filled with a mixture of 300ml of lemon juice, and the mixture was allowed to steep in a warm location for 24 hours. After 24 hours, the mixture was strained and risen with water then spread on a baking tray. Dry it in the oven until it is completely dried. The combination of the lemon juice along with the heat will activate the banana peel carbon. The testing of the battery is done using a multimeter to get the voltage and current to light up the load. A scanning electron microscope is used to characterize the banana’s active carbon. This study proves that using natural processes can active the carbon and become alternative energy for the future.